Synthesis, characterization and reactivity studies of bio-inspired nickel based acireductone dioxygenase model complexes / Shubham - Shubham (IISER Mohali, 2022)
C-C bond cleaving reactions are very slow due the inertness of the bonds. However nature utilises metalloenzymes like ARD to cleave aliphatic c-c bonds effectively in presence of dioxygen. The ARD active site has N 3 O (3His,1Glu) coordination environment with two water molecules. This work is inspired by the activity and active site of ARD. In this context some mononuclear nickel(II) and cobalt(II) synthetic complexes were synthesised with N3O coordination from ligand. The substrate binding to this model complexes were studied and characterised by spectroscopic techniques.
Keywords: characterization; reactivity studies; acireductone; dioxygenase